Co-editors' introduction - KAUFFMAN, Robert John (Institutional Knowledge at Singapore Management University, 2008)
The contents of this special issue were conceptualized in 2005 by mobile payments specialists, Stamatis Karnouskos of SAP AG in Germany, Elaine Lawrence of the University of Technology Sydney in Australia, and Key Pousttchi of the University of Augsburg in Germany. Later, ECRA’s Coordinating Editor, Rob Kauffman, who is also an expert in the area of electronic payments and financial services, joined the group to support the development of a special issue from the ECRA side. The result is the present issue, entitled ‘Research Advances for the Mobile Payments Arena.’ It brings together contributions and new research from leading scholars and industry professionals from Europe, the Asia Pacific region and the United States. The guest co-editors have offered a complete overview of the contents of the special issue, as well as the process they used to develop it. The co-editors of ECRA offer their thanks to the guest editors for doing an outstanding job in developing this special issue, and encourage other university researchers, and business and consulting professionals to contribute new articles on mobile payments and mobile commerce for publication in this journal.The sole regular article that appears in this issue is entitled ‘Experiences in Developing a Fair-Exchange E-Commerce Protocol Using Common Off-the-Shelf Components.’ The authors, Indrajit Ray and Hongjun Zhang of the Colorado State University, explore the issue of ‘fair-exchange’ as a means to formulate a effective protocols for transaction-making in electronic commerce that are trust-preserving for buyers and sellers on the Internet. The essence of the authors’ perspective is that some kind of effective mechanism design is required to balance the interest of the participants, for example, by permitting the buyer to validate the characteristics of the product that is to be consumed before actually paying for it. The basis for the technical innovation that the authors present is known as the ‘theory of cross validation.’ The theory is based on the availability of ‘asymmetric encryption technology,’ which itself is developed from the well-known RSA encryption. The authors contend that the application of this theory in mechanism design for value exchange via the Internet ensures that both buyers and sellers are not subject to any sort of foul play that could lead to post-transaction regret or a desire to unwind the transaction. The authors develop the analytical and modeling background for their innovation, establish a basis for the ‘validated receipt property’ of their protocol, and show what the nature of the built-in security protection is. They describe their protocol in detail, and illustrate how it works. They also provide a proof for why the protocol ensures fair-exchange. An especially interesting aspect of the authors’ work is presented via the system and logical architectures for the operation of a trial e-commerce environment that does fair-exchange protocol-based payment validation. The authors’ work is funded by the National Science Foundation in the context of a larger project related to Internet exchange, exchange protocols and security.The special issue project that we described above, process-wise, is an exemplar for how we would like to work with prospective guest editors who bring new ideas for special issues to our attention. Wherever possible, we would like to have involvement from leading scholars around the world, who have well-established research records or significant industry background and knowledge. We encourage guest editors to make proposals in writing to the senior editorial team of ECRA. This process normally requires the people who propose a special issue to develop a ‘call for papers,’ prepare a time-line of activities, suggest an advisory board for the special issue of other senior scholars and industry professionals, and to identify potential members of a special issue editorial board. Wherever it’s possible, we usually ask that special issue guest editors work through pre-committed AEs, so that they can cover the reviewing requirements that arise for special issue submissions, without drawing upon the regular members of ECRA’s standing editorial board. This has an added benefit in that it helps the journal to identify new members of its editorial board, and encourage longer-term participation.We currently have two additional special issues under development at this time. One is on the topic of ‘Supply Chain Trading,’ with a particular focus on the International ‘Trading Agent Competition for Supply Chain Management’ (TAC-SCM). The issue is being constructed under the guidance of the past-Coordinating Editor of ECRA, Norman Sadeh of Carnegie Mellon University, in partnership with John Collins of the University of Minnesota and Sverker Janson of the Swedish Institute of Computer Science. Norman Sadeh and John Collins are both long-time participants (and competitors) in TAC-SCM. This competition has been of increasing interest to the Artificial Intelligence, Electronic Commerce, and Multi-Agent Systems research communities. An overview of TAC-SCM is available at www.sics.se/tac/page.php?id=13, and a full specification is included at the following related URL, www.sics.se/tac/tac07scmspec.pdf. The details for the 2008 edition of the game can be found at www.sics.se/tac/page.php?id=72.A second special issue is in the midst of kicking off. ECRA Co-Editor, Chris Westland of the University of Illinois, Chicago, in cooperation with Julie Smith-David of Arizona State University, and Bin Wang of the University of Texas, Pan American, currently have a call for papers out on the topic of ‘Social Networks and Web 2.0.’ The guest editors have written: ‘Web 2.0 has enabled a new generation of Web-based communities, social networks, wikis, hosted services and folksonomies to facilitate collaboration and sharing among users. These are characterized by open communication, decentralization of authority, and freedom to share and reuse. Web 2.0 refers to a set of collaborative applications and mashups with a social approach to generating and distributing Web content. Web 2.0 applications provide a basis for social networks, where users share and filter content, collaborate, seek information, and interact on the Web. … We welcome theoretical, analytical, case study, empirical, and other methodological works that support contributions relating to specific classes of applications, as well as to cross-disciplinary and cross-paradigm research.’ The senior editors of ECRA are especially interested to promote this special issue as a basis for encouraging the cross-disciplinary community of researchers and professionals to participate. The guest editors are in the midst of soliciting manuscripts from Computer Science, Communications and Media, Sociology, Information Systems, Marketing, Strategy, and other related disciplines, and hope to find a new and interesting synthesis in the works they showcase in the completed special issue.The senior editors would like to thank Ms. Arti Mann, ECRA’s Editorial Assistant, for her service to the journal. Although she is just beginning her work since January 2008, she has been instrumental already in assisting us with ensuring that reviews get done on time, submitted papers are properly assigned to ECRA’s AEs, and that our editorial board is able to get hooked up with the publisher’s staff at Elsevier for proper training in the use of the Elsevier Editorial System (EES), ECRA’s electronic reviewing system. Arti, we appreciate all the help that you’re giving to the journal.As we move from spring to summer, all of us in the university community typically gear up for some much-needed down-time. ‘Down-time’ is an interesting concept for most of us though. It’s when we’re able to devote the most time to our research, take time to establish new projects, and also catch up on other projects that have become overdue. The summer is also a good time for us to plan the efforts that we will make in the coming year with research, in particular, what we hope to complete, submit to and publish in leading conferences and journals. With this in mind, the senior editors of ECRA would like to extend to you a warm invitation to submit your research for review at this journal. We are open to technical and managerial works, but especially appreciate the research and writing of authors who possess the ability to blend the two, and make what we publish in the pages of ECRA of interest to the broadest possible research and practitioner community. In addition, at this time, we are especially in need of volunteers to help out with the reviewing of manuscripts that are submitted to ECRA. Areas where we have special needs include digital cryptography, public-key encryption protocols, mobile payments technologies, and recommender systems and collaborative filtering. We are also interested to engage scholars who have strong knowledge in the methods of survey research, partial least squares, structural equation modeling, game theory, and econometrics methods.Best wishes on your summer projects this year!